Measuring capital adequacy supervisory stress tests in a Basel world - Larry D. Wall (Federal Reserve Bank of Atlanta, 2013)
The United States is now committed to using two relatively sophisticated approaches to measuring capital adequacy: Basel III and stress tests. This paper shows how stress testing could mitigate weaknesses in the way Basel III measures credit and interest rate risk, the way it measures bank capital, and the way it creates countercyclical capital buffers. However, this paper also emphasizes the extent to which stress tests add value will depend upon the exercise of supervisor discretion in the design of stress scenarios. Whether supervisors will use this discretion more effectively than they have used other tools in the past remains to be seen.
Keywords: G01; G21; G28; E50; 330; capital adequacy; Basel capital ratios; stress test